2009
DOI: 10.1007/s00125-009-1456-y
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal hormone therapy and new-onset diabetes in the French Etude Epidemiologique de Femmes de la Mutuelle Générale de l’Education Nationale (E3N) cohort

Abstract: Aims/hypothesis Two US randomised trials found a lower incidence of type 2 diabetes in women treated by menopausal hormone therapy (MHT) with oral conjugated equine oestrogen combined with medroxyprogesterone acetate. The purpose of this study was to evaluate the influence of various MHTs, according to their formulation and route of administration, on new-onset diabetes in a cohort of postmenopausal French women. Methods The association between MHT use and new-onset diabetes was investigated by Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 39 publications
0
43
0
2
Order By: Relevance
“…For example, in women both subphysiologic and supraphysiologic estrogen levels associate with insulin resistance and type 2 diabetes mellitus; but, in men the association is strongest with high estrogen and low testosterone levels. 6366 However, these findings do not provide the precise mechanistic link between sex hormones, cellular and systemic metabolic abnormalities and PAH. MicroRNAs (miRNAs; miRs) are short, single-stranded non-protein coding gene products typically 20–22 nucleotides in length that post-transcriptionally regulate the expression of target genes through interactions with specific mRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in women both subphysiologic and supraphysiologic estrogen levels associate with insulin resistance and type 2 diabetes mellitus; but, in men the association is strongest with high estrogen and low testosterone levels. 6366 However, these findings do not provide the precise mechanistic link between sex hormones, cellular and systemic metabolic abnormalities and PAH. MicroRNAs (miRNAs; miRs) are short, single-stranded non-protein coding gene products typically 20–22 nucleotides in length that post-transcriptionally regulate the expression of target genes through interactions with specific mRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that most of these large epidemiological studies used combination hormone therapy (CEE + MPA), so it is also unclear how well the results generalize to other HT regimens. Several recent prospective cohort studies have also found reduced incidence of new-onset diabetes in women taking HT (de Lauzon-Guillain et al, 2009; Pentti et al, 2009); this effect was much stronger for women taking oral HT vs. transdermal HT (de Lauzon-Guillain et al, 2009) and for women who had long-term HT exposure (Pentti et al, 2009). In the WHI trial, women with larger waist circumference measurements showed a greater beneficial effect of HT on decreasing diabetes risk (Margolis et al, 2004).…”
Section: Estrogen Regulation Of Whole-body Metabolismmentioning
confidence: 95%
“…Moreover, estrogen receptor activation in both cultured rodent and human islet cells inhibits the synthesis and accumulation of intracellular lipids that may contribute to β-cell failure [31]. Although the meta-analysis by Ding et al revealed a positive association between endogenous estradiol levels and the risk of T2DM, independent of body mass index (BMI), in both men and post-menopausal women [26], human studies involving exogenous hormone administration have suggested a protective role of estrogen on T2DM, at least in women [32,33]. For example, a trial of 2,029 women randomized to either placebo or 0.625mg of conjugated estrogen with 2.5mg medroxyprogesterone acetate, revealed a 6.2% incidence of diabetes in the hormone-treated group over 4 years of follow-up, compared with an incidence of 9.5% in the placebo group [32].…”
Section: Associations Of Sex Hormones Circulating Levels Of Shbg Anmentioning
confidence: 99%
“…For example, a trial of 2,029 women randomized to either placebo or 0.625mg of conjugated estrogen with 2.5mg medroxyprogesterone acetate, revealed a 6.2% incidence of diabetes in the hormone-treated group over 4 years of follow-up, compared with an incidence of 9.5% in the placebo group [32]. Similarly, in a subsequent analysis of a large prospective study involving 63,624 postmenopausal French women published by de Lauzon-Guillain and colleagues, estrogen replacement was associated with a reduction in diabetes risk compared with women never treated with replacement therapy (hazard ratio [HR] 0.82; 95% CI, 0.72–0.93) [33]. Moreover, oral estrogen replacement was associated with larger reductions in the risk of T2DM (HR 0.68; 95% CI, 0.55–0.85) than transdermal estrogen (HR 0.87; 95% CI, 0.75–1.00) [33], suggesting that the method of exogenous estrogen exposure may modulate the hormone’s potential anti-diabetic effects.…”
Section: Associations Of Sex Hormones Circulating Levels Of Shbg Anmentioning
confidence: 99%